2013
DOI: 10.1155/2013/716545
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thermo‐ and Detergent Stable Antigenic Glycosylated Cysteine Protease of Euphorbia nivulia Buch.‐Ham. and Evaluation of Its Ecofriendly Applications

Abstract: An antigenic glycosylated cysteine protease has been purified from the latex of Euphorbia nivulia Buch.-Ham. It exhibits remarkable protease activity in the presence of metal ions, oxidizing agents, organic solvents, and detergents. This enzyme showed potential role in leather processing industry due to its dehairing activity for animal hide without hydrolyzing fibrous proteins, producing, by this way, a better quality product. The enzyme can also be used for silver recovering from X-ray plates. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The influence of surfactants (SDS, Tween 20 & 80, and Triton X-100) on G. stearothermophilus protease stability was also examined. Specificity of our protease reduced remarkably after an addition of different concentrations of Triton X-100 and residual activity declined to 34% after addition of 1% Triton X-100 [59]. Sung et al [60] and Haddar et al [61] have reported similar results with decreased activity of proteases from B. subtilis and B. mojavensis A21 after an addition of 0.01% Tween 20 and Triton-X100, by 53 and 92%, respectively.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The influence of surfactants (SDS, Tween 20 & 80, and Triton X-100) on G. stearothermophilus protease stability was also examined. Specificity of our protease reduced remarkably after an addition of different concentrations of Triton X-100 and residual activity declined to 34% after addition of 1% Triton X-100 [59]. Sung et al [60] and Haddar et al [61] have reported similar results with decreased activity of proteases from B. subtilis and B. mojavensis A21 after an addition of 0.01% Tween 20 and Triton-X100, by 53 and 92%, respectively.…”
Section: Discussionsupporting
confidence: 71%
“…The influence of surfactants (SDS, Tween 20 & 80, and Triton X‐100) on G. stearothermophilus protease stability was also examined. Specificity of our protease reduced remarkably after an addition of different concentrations of Triton X‐100 and residual activity declined to 34% after addition of 1% Triton X‐100 . Sung et al .…”
Section: Discussionmentioning
confidence: 71%
“…A number of studies have demonstrated the nematicidal effect of latex proteases from plants (Badgujar and Mahajan, 2013;Stepek et al, 2007;Sufiate et al, 2017b). However, this is the first report on nematicidal effect of S. grantii.…”
Section: Resultsmentioning
confidence: 82%
“…DCM as a polar aprotic solvent decreased proteolytic activity of all lyophilized enzyme preparations at 2.5% and 5% (v/v) of concentration. Badgujar et al [25] reported that the proteolytic activity of cysteine protease was decreased with DCM. Ethanol as hydrophilic organic solvent and hexane and toluene as aprotic nonpolar organic solvents have increased proteolytic activity of lyophilized enzyme preparations with pumice and KCl.…”
Section: Organic Solvents Effect On Lyophilized Protease Preparationsmentioning
confidence: 99%